PELAKSANAAN METODE MUROJA’AH TAHFIDZ AL-QUR’AN DI MA’HAD AL-ULYA MAN KOTA BATU - Faizatul Mukholisoh; Anwar Sa’dullah; Nur Hasan (Vicratina : Jurnal Ilmiah Keagamaan, 2019)
In this study the researchers discussed the Implementation of the Muroja'ah Tahfidz Al-Qur'an Method in Ma’had MAN Batu City. The focus of the issues discussed in this study are 1) How is the ability to memorize the Qur'an with the murojaa'ah method in Ma’had Al-Ulya MAN Kota Batu. 2) How is the process of implementing memorizing the Qur'an with the method of muroja'ah in Ma’had Al-Ulya MAN Kota Batu. 3) What are the obstacles to memorizing the Qur'an with the method of muroja'ah for santri in Ma’had Al-Ulya MAN Kota Batu. In this study using a qualitative research approach and descriptive type of research. Where in this study when collecting data using the method of observation, interviews, and documentation. At the time of the research, the results of the study were as follows: the ability of the santri to memorize the Qur'an using the muroja'ah method was different, some were fluent and fluent both in terms of tajwid and makhorijul letters, but there were also students who still needed guidance from ustadzah. The process of implementing the muroja'ah method is done every Monday, Tuesday, Thursday and Friday after the morning prayer for additional deposits, while for muroja'ah memorizing long after prayer is done 'in the ma'had hall. The obstacles experienced by the santri in the implementation of the muroja'ah method were forgetfulness, saturation and boredom, and laziness.